Institutionalization of Ukraine’s information policy as a function of strategic communication - Piechota, Grażyna; Rajczyk, Robert (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2018)
The paper presents the contemporary information policy implemented by the Ukrainian government. The survey answers the question about the new role of information policy in the state authorities’ activities. The research focuses on the executive branch of power, due to its impact on the internal and external image of Ukraine. The analysis was conducted at the strategic, institutional and operational levels, and concerned the content of messages.